2018
DOI: 10.1089/tmj.2017.0046
|View full text |Cite
|
Sign up to set email alerts
|

Remote Monitoring of Automated Peritoneal Dialysis Patients: Assessing Clinical and Economic Value

Abstract: In a simulated environment, early intervention enabled by RTM reduced healthcare resource utilization and associated costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…These benefits have been obtained at the same time with a reduction of in-person visits, maintaining the patient at home with excellent results. These results are in accordance with Nayak et al [13]: they speculated that RM of patients on APD offers benefits of real-time monitoring of the therapy, assuring patient safety through the surveillance of critical portions of the treatments, and, on the other hand, enabling early detection of noncompliance [10]. A system with 2-way communications and with an interactive interface allows a fast “troubleshooting” for problems: the physicians can change the prescription online, reducing the frequency of in-person visits to a PD center [13, 14].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These benefits have been obtained at the same time with a reduction of in-person visits, maintaining the patient at home with excellent results. These results are in accordance with Nayak et al [13]: they speculated that RM of patients on APD offers benefits of real-time monitoring of the therapy, assuring patient safety through the surveillance of critical portions of the treatments, and, on the other hand, enabling early detection of noncompliance [10]. A system with 2-way communications and with an interactive interface allows a fast “troubleshooting” for problems: the physicians can change the prescription online, reducing the frequency of in-person visits to a PD center [13, 14].…”
Section: Discussionsupporting
confidence: 90%
“…Addressing non-adherence and understanding barriers to self-care are critical in order to address this issue and RM and telemedicine may help in this regard. Indeed, in a recent study, Makhija et al[10] speculated that early intervention enabled by RM can reduce healthcare resource utilization and associated costs.…”
Section: Introductionmentioning
confidence: 99%
“…Another study of 269 patients on PD who received an intervention of daily RTM of BP and weight coupled with video conferencing telehealth care showed that the adjusted risk of hospital admission was 46% (odds ratio, 0.54; 95% CI, 0.33 to 0.89) lower and hospital days was 54% (odds ratio, 0.46; 95% CI, 0.26 to 0.81) lower compared with before the intervention (15). It has been estimated that adoption of RTM systems to monitor PD treatments may also yield some economic benefits to healthcare systems in various countries (13,15). The influence of RTM on technique failure rates has not been reported previously in PD, yet the improvements we found are consistent with observations from RTM in the home HD population (16).…”
Section: Discussionmentioning
confidence: 99%
“…Remote monitoring systems broadly include an array of technologies and processes in the areas of telemedicine/telehealth such as telephonic/video assessments, connected health sensors, and health record portals (6). Prior reports of various types of remote monitoring systems tested in the PD population suggest they associate with improvements in patient satisfaction, quality of life, nutrition, exit-site infection rates, peritonitis rates, and hospitalization rates (7)(8)(9)(10)(11)(12)(13). However, patient groups included in the evaluations of remote monitoring systems to date are small and the findings may not be generalizable.…”
Section: Introductionmentioning
confidence: 99%
“…Our results confirm the data described by Wallace et al [16] who reported that replacing the face-to-face encounter with a telehealth monitor can reduce patient driving time, time spent in waiting rooms, and travel costs. In this context, Makhija et al [17] performed a study based on a simulated environment and estimated the reduction of health-care resource utilization and associated costs by early intervention using RM on APD patients.…”
Section: Discussionmentioning
confidence: 99%